The Pattern of Stability and Change in Parental Locus of Control Over 6 Years and Teacher Ratings of Child Behavior - Nowicki, Stephen; Gregory, Steven; Ellis, Genette L.; Iles-Caven, Yasmin; Golding, Jean (Frontiers in Psychology, 2018)
A previous study from our group showed that parents’ locus of control (LOC) obtained before the birth of their child was associated with the child’s behavior at school in School Years 3 (ages 7–8) and 6 (ages 10–11). Here we examine whether a change in parental LOC over the first 6 years of the child’s life was associated with differences in his or her behavior as rated by their teachers. As before, we use data from the Avon Longitudinal Study of Parents and Children (ALSPAC). A modified version of the adult Nowicki–Strickland internal–external LOC scale was completed by mothers and fathers in their own home during pregnancy and 6 years later. Externality was defined as a score greater than the median and internality as equal to, or less than, the median. Outcomes were the five individual subscales and the total difficulties of Goodman’s Strengths and Difficulties Questionnaire (SDQ) completed by the children’s class teachers at the end of School Years 3 and 6. As predicted, we found that parents who remained externally oriented, or became external, had children with more behavioral difficulties in primary school compared with parents who remained or became internal. Type of behavior difficulties varied somewhat with whether mothers or fathers remained or changed toward externality. These results support the possibility that changes in parental LOC are associated with children’s personal and social adjustment. Consequently, programs to change parental LOC may be worth evaluating.